Effect of technology addiction prevention psychoeducation program on 8th grade students - Karadağ, Yunus Emre; Noyan, Cemal Onur (Journal of Dependence, 2023)
Objective: The aim of the study was to examine the effect of the psychoeducation program developed to prevent technology addiction on 8th grade students' internet addiction levels, self-efficacy levels and daily technology use time. Method: Internet Addiction Scale, Middle School Self-Efficacy Scale and Personal Information Form were used to collect data. In order to test the effectiveness of the psychoeducation program developed based on the relevant literature, a quasi-experimental design with pretest and posttest measurements, experimental and control groups (2x2) was used. The study group of the research was composed of 20 students who were determined to be at risk for internet addiction and who volunteered to participate in the research, divided into two equal groups as experimental and control groups. The 4-session psychoeducation program developed within the scope of the research, each lasting approximately 60 minutes, was applied online once a week to the adolescents in the experimental group, while no intervention was made to the control group.Results: The psychoeducation program was found to be effective in reducing the internet addiction levels and daily technology use time of the adolescents participating in the study, but it did not have a significant effect on the selfefficacy levels of the students.Conclusion: Psychoeducation program developed within the scope of the research is an effective tool in preventing problematic technology use of adolescents participating in the study and reducing the time they spend on technology.
Keywords: Technology addiction; psychoeducation; adolescents